Schwannoma of the seminal vesicle: Case report and review of the literature - César Mínguez Ojeda; Jennifer Brasero Burgos; Angie Tenelanda Santillan; Ana Saiz; Ana Cristina Tagalos Muñoz; Jose Daniel Subiela; Alvaro Sanchez Gonzalez; Alberto Artiles Medina; Enrique Sanz Mayayo; Rafael Rodriguez Patrón; Miguel Angel Jimenez Cidre; Francisco Javier Burgos Revilla (Urology Case Reports, 2023)
Seminal vesicles can be affected by tumours originating in other locations. However, primary tumours of the seminal vesicle are extremely rare, with less than 100 cases reported in literature. Seminal vesicle adenocarcinoma is the most common type, but there are also other malign lesions. Diagnosis is challenging due to the lack of early symptoms and well-defined criteria. These tumours are usually asymptomatic and discovered incidentally during imaging tests or pelvic surgery. Definitive diagnosis requires anatomopathological analysis. Case report of 58-years-old man with schwannoma of the seminal vesicle. We describe the main characteristics of these tumours as well as their therapeutic approach.